Pengaruh Model Problem Based Learning berbasis Assemblr EDU Augmented Reality terhadap Hasil Belajar Geometri Siswa Kelas VII - Ruslan, Ruslan; Djam’an, Nurwati; Muhtar, Muh. Nur Ghani Ilham (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2024)
This research is a quasi-experimental research that aims to examine: (1) student learning outcomes after the applying of problem-based learning model that base on Assemblr EDU Augmented Reality; (2) student learning outcomes after the applying of problem based learning model without Assemblr EDU Augmented Reality; (3) Is the use of problem based learning model that based on Assemblr EDU Augmented Reality has an effect on learning outcomes of geometry compared to without Assemblr EDU Augmented Reality. The researcher used the Simple Random Sampling technique that selecting two classes from the population and determining the experimental class and the comparison class. Data obtained from the test of learning outcomes. Data were analyzed using descriptive and inferential statistical analysis. The result of the descriptive statistical analysis is the students’ learning outcomes average in geometry with problem based learning model that based on Assemblr EDU Augmented Reality is higher than learning without Assemblr EDU Augmented Reality. The result of inferential statistical analysis is the learning outcomes in geometry that achieved by the using of problem based learning model that based on Assemblr EDU Augmented Reality are not better than learning without Assemblr EDU Augmented Reality